Cognitive Behavioral Therapy of a Generalized Anxiety Disorder Case Comorbid with Health Anxiety - Nalan Kara (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Introduction: Generalized Anxiety Disorder (GAD) is a chronic psychiatric disorder which affects the person’s quality of life. It is often seen with other psychiatric disorders and this complicates the diagnosis, tretment and prognosis. In this case report Cognitive Behavioral Therapy (CBT) of a GAD patient comorbid with health anxiety was introduced and the place of CBT in these conditions was discussed. Case: Twenty four year-old, single male patient was referred for worries abouth health and other life conditions. Seven years ago he started to find out several physical symptoms (abdominal paint, nausea) in his body; because of these symptoms he thought he will become ill, undergo surgical operation and die. He frequently consulted the doctors, releived as they didn’t find any illness, but his fears reoccured whenever he complained any symptom. Besides health anxiety, he feared to encounter bad occurrences. Paroxetine 20 mg/day prescribed and besides drug treatment CBT was started. CBT process begun with evaluation and case formulation, the aims of therapy were established and psycoeducation for CBT and anxiety was given. Repeated doctor consultations were prevented by exposure-response prevention (ERP). Cognitive restructering technics were used for health and other worries. Conclusion: CBT alone or in addition to pharmacotherapy may be an effective treatment option for GAD with health anxiety. [JCBPR 2014; 3(2.000): 99-108]